Reading and Listening Ability Relative to Students’ Level of Performance - Maria Aurora G. Victoriano; Matilda H. Dimaano (International Journal of Educational Management and Development Studies, 2023)
The study aimed to determine the second language reading and listening abilities of Grade 11 students and their relationship to grammatical morphemes and lexico-grammatical knowledge by proposing engagement exercises to enhance students’ language performance in public secondary schools. The study used the descriptive research method to determine students’ performance levels in reading, and listening abilities. The respondents were grade 11 students enrolled in the selected secondary schools in the Division of Capiz. Purposive sampling method was used as this study is based upon various criteria, including the capacity and willingness of respondents to participate. The data-gathering instruments utilized in the study were documentary analysis and teacher-made tests. For a meaningful interpretation and analysis of the study, the data were subjected to statistical treatment such as frequency, percentage, ranking, mean, Pearson r product-moment correlation, and T-test. The study’s findings revealed that Grade 11 students’ performance levels are average in grammatical morphemes and lexico-grammatical knowledge, while the levels of students’ reading and listening abilities are generally average. Further, there are relationships between the reading and listening abilities and their socio-demographic attributes. The study recommends language engagement exercises that includes activities that could enhance the listening and reading abilities of Grade 11 students based on the areas needing enhancement.